The Position of Land Certificates as Proof of Ownership in Resolving Land Rights Disputes in Mining Areas - Pondiu, Rifky Rachel; Prayitno, Ahmad Hadi (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. The position of land certificates as proof of ownership in resolving land rights disputes in mining areas still has problems, namely the emergence of perceptions that are dismissive of authentic deeds. In fact, this will give rise to the dynamics of land law in society. The objectives of this study are to analyze: 1). The legal force of the land certificate is examined in relation to land rights in the mining business permit area. 2). The role of Notaries in using land certificates as proof of ownership. The approach method used in discussing this research problem is a normative juridical research type.The research specification used is analytical descriptive research. The type of data uses primary and secondary data. The data analysis method used in this study is qualitative data analysis. The results of the study concluded: First, theoretically the position of SKT is a weak evidence, because it is made underhand without going through a legalization process by a Notary official, considering that only a Notary can issue an authentic deed. Second, there is a gap between theory and practice, with the reason that in practice judges often disregard authentic deeds in adjudicating land dispute cases. This can be seen in Decision Number: 24 / G / 2014 / PTUN.KDI and Decision Number: 27 / G / 2016. PTUN. KDI. Keywords: Land Certificate; Notary; Ownership.